Exploring the Factors that Influence Pivoting in Student Startups: A Case Study of Entrepreneurship Student of SBM ITB Analysis - Esther Ariella (CV. Syntax Corporation Indonesia, 2023)
According to recent news sources and journals, the growth of start-ups in today's world is on the rise. The pandemic has played a significant role in this growth, with many people starting their own businesses after being laid off from their jobs (Casselman, 2021). In 2023, experts predict that there will be increased investment in social media, user-generated content, and entertainment for small businesses (Halperin, 2023). Alternative funding sources are also becoming more common for small businesses as interest rates rise (Halperin, 2023). The design acts as the research project's